Sabbatical Leave Fall 2012 Follow-up Report - Sampson, Linda (Distribution: Fall 2012 ; Communication., 2012)
The objective was to collect and analyze some exploratory data for research on "Exploring incivility in interpersonal relationships." The collected data provided material for two papers to be delivered at a national and international conference in 2013.
Keywords: dept.com; faculty_collection; sabbatical_report

Music in American Combat Films a Critical Study - O'Brien, Wesley J. (McFarland & Co., McFarland, 2012)
"The book explores ways combat film scores interact collaboratively with other film elements (for instance, image and dialogue) to guide audience understanding of theme and character. Examined are classical and current models of film scoring practice and the ways they work to represent changes in film narratives taking place over time or from film to film"--Provided by publisher.
Keywords: History and criticism; History and criticism; War films; Motion picture music; United States; dept.com; faculty_collection